Exploring the Entrepreneurial Knowledge, Skills, and Mindset of Jordanian University Engineering Graduates to Enhance Career Prospects - Alkhawaldeh, Khleef A.; Dabaghie, Yana M. (Journal of Engineering Education Transformations, 2025)
This study examined the entrepreneurial knowledge and skills of engineering graduates and the entrepreneurial mindset of engineers. It also examined how entrepreneurial knowledge and skills affect the mindset of the entrepreneurial engineer. The study population consists of twenty-five Jordanian public and private universities that offer engineering programs. Based on the results of an overview of the engineering study plans of these universities, four universities were selected (The University of Jordan, Princess Sumaya University for Technology, Al- Hussein Technical University, Al-Hussein Technical University, Al-Ahliyya Amman University). The total number of engineering graduates participating in this study and whose responses were valid for the analysis was 65 students who graduated between 2016 and 2022. The results of this study indicated that the average entrepreneurial knowledge and skills of engineering graduates ranged between average and good. The findings also indicated that there is a statistically significant positive correlation between the entrepreneurial knowledge and skills of engineering graduates and their entrepreneurial mindset. The study concluded that it is essential for undergraduate engineering students to acquire entrepreneurial knowledge and skills that support their engineering major, and lead them to think broadly about their future careers and opportunities. Thus, entrepreneurial knowledge and skills enhance their competitiveness in innovative and rapidly emerging engineering industries. The study recommended the inclusion of entrepreneurship knowledge and skills in all engineering curricula and courses in universities.